Analysis Of Merchandise Inventory Accounting At Mini Market Sirajudin, Bintuhan, Kaur Regency - Concesa, Maria; Hidayah, Nenden Restu; Subhi, Ramadan (Utami Publisher, 2025)
Sirajudin Mini Market is a retail business inBintuhan, Kaur Regency, which sells various basic necessities for the community, wheremerchandise inventory is a major asset that affectssmooth operations and business profits. However, inventory recording atthis minimarket is still done in a simple manner and does not fully comply withapplicable accounting standards. This study aims to determine the application ofmerchandise inventory accounting at Sirajudin Mini Market and its conformitywith accounting theory and Financial Accounting Standards for Micro, Small, andMedium Entities. This study uses a descriptive comparative qualitative approachwith data collection techniques through interviews, observation, anddocumentation. The analysis was conducted by comparing the conditions in the field with Mulyadi's (2016) theory, which covers six main aspects, namely recording the costof finished goods sold, purchases, purchase returns, warehouse goods requests andexpenses, goods returns, and physical inventory calculations. The results of the study show that stock controlhas been carried out through warehouse cards and routine physical checks, buttransaction recording has not been carried out through a general journal and has not beencomputerized, so there is still a risk of errors. Therefore,it is recommended that Sirajudin Mini Market start using an inventory recording applicationsuch as Zahir so that the recording process becomes more accurate, efficient,and easier to control.